New insights about theropod palaeobiodiversity in the Iberian Peninsula and Europe: Spinosaurid teeth (Theropoda, Megalosauroidea) from the Lower Cretaceous of La Rioja (Spain). (December 2020) - Isasmendi, E.; Sáez-Benito, P.; Torices, A.; Navarro-Lorbés, P.; Pereda-Suberbiola, X.
Abstract: Twelve isolated spinosaurid teeth from the Enciso Group of the eastern Cameros Basin (La Rioja, Spain) have been studied. The fossil material has been found in five sites near the town of Igea, where a fluvio-lacustrine system with marine influence was developed during the Barremian-early Aptian. Besides the study of the qualitative and quantitative features of the teeth, morphometric analyses have also been carried out. The teeth from La Rioja seem different from those of Baryonyx and are attributed to Baryonychinae indet. Ten of the baryonychine teeth show serrated mesial carinae, but two specimens lack denticles in it, which indicates the presence of two different baryonychine morphotypes in Igea, similar to that observed in other contemporaneous Iberian sites. The spinosaurid remains from La Rioja support the idea of a land bridge between Europe and Gondwana. Furthermore, these findings do also back that spinosaurids inhabited freshwater environments with marine influence or next to coastal zones. Highlights: La Rioja baryonychine teeth are different from those of Baryonyx. Two morphotypes are present in Igea and resemble those of other Iberian sites. Trevijano spinosaurine teeth are the largest in size of the Iberian Peninsula. Faunal interchange between Africa and Europe is supported by spinosaurid record. La Rioja spinosaurids lived in freshwater environments with marine influence.